2021
DOI: 10.1155/2021/9913798
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Selected Matrix Metalloproteinases (MMPs) and Correlation with Cytokines in Psoriatic Patients

Abstract: Metalloproteinases (MMPs) and cytokines have a great impact on the pathogenesis of psoriasis. Cytokines, as key mediators of inflammation and autoimmune processes, play a crucial role in the regulation of MMP expression in different cell types. Parallel, MMPs have an influence on cytokine production. This interaction was not well recognized in psoriatic patients. Our study is aimed at assessing the selected serum MMP levels and their correlations with cytokine levels in the serum of psoriatic patients. We obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…According to previous work, such MMP-responsive linkers should be readily cleaved by a range of MMPs, including MMP-9 and MMP-7. , A range of other proteases are also present in skin, including human leukocyte elastase, proteinase 3, and cathepsin G. A cleavage site specificity study performed on tropoelastin showed, however, that these proteases do not have a high preference for Leu in P1′, Pro in P3, or Gly in P3′, hence no interference from such enzymes to the performance of the presently investigated system is expected. To provide a proof of concept, we chose to add activated MMP-9 in a concentration of 80 nM, which represents a physiologically relevant concentration of collectively acting subtypes of MMPs in the dermis during inflammation in vivo . Due to autocatalysis, MMP-9 activity is present only transiently .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous work, such MMP-responsive linkers should be readily cleaved by a range of MMPs, including MMP-9 and MMP-7. , A range of other proteases are also present in skin, including human leukocyte elastase, proteinase 3, and cathepsin G. A cleavage site specificity study performed on tropoelastin showed, however, that these proteases do not have a high preference for Leu in P1′, Pro in P3, or Gly in P3′, hence no interference from such enzymes to the performance of the presently investigated system is expected. To provide a proof of concept, we chose to add activated MMP-9 in a concentration of 80 nM, which represents a physiologically relevant concentration of collectively acting subtypes of MMPs in the dermis during inflammation in vivo . Due to autocatalysis, MMP-9 activity is present only transiently .…”
Section: Discussionmentioning
confidence: 99%
“…To provide a proof of concept, we chose to add activated MMP-9 in a concentration of 80 nM, which represents a physiologically relevant concentration of collectively acting subtypes of MMPs in the dermis during inflammation in vivo. 27 Due to autocatalysis, MMP-9 activity is present only transiently. 51 To mimic the inflammatory relapsing course seen for many skin diseases, MMP-9 was therefore added multiple times.…”
Section: Characterization Of the Microparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…106 There has been further evidence of increased expression of MMP genes in human psoriatic lesions and human keratinocytes cultured with IL-17. 107,108 Specifically, elevated levels of MMP-9 and pro-MMP-1 levels were observed in patients' serum, and MMP-3 was further correlated with cytokines IL-4, IL-17A, TNF-α in psoriatic patients. 107,109,110 In addition, the HPA axis may be implicated in psoriasis.…”
Section: Psoriasis Psychiatric Co-morbiditiesmentioning
confidence: 94%
“…107,108 Specifically, elevated levels of MMP-9 and pro-MMP-1 levels were observed in patients' serum, and MMP-3 was further correlated with cytokines IL-4, IL-17A, TNF-α in psoriatic patients. 107,109,110 In addition, the HPA axis may be implicated in psoriasis. 104 CRH has been shown to be involved in a number of cutaneous roles including stimulation of IL-6 and IL-11 production and activation of pro-inflammatory complex protein of NF-kβ, ultimately priming keratinocytes for a proinflammatory state.…”
Section: Psoriasis Psychiatric Co-morbiditiesmentioning
confidence: 94%